2021
DOI: 10.3390/cancers13194910
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver Agreement of PD-L1/SP142 Immunohistochemistry and Tumor-Infiltrating Lymphocytes (TILs) in Distant Metastases of Triple-Negative Breast Cancer: A Proof-of-Concept Study. A Report on Behalf of the International Immuno-Oncology Biomarker Working Group

Abstract: Patients with advanced triple-negative breast cancer (TNBC) benefit from treatment with atezolizumab, provided that the tumor contains ≥1% of PD-L1/SP142-positive immune cells. Numbers of tumor-infiltrating lymphocytes (TILs) vary strongly according to the anatomic localization of TNBC metastases. We investigated inter-pathologist agreement in the assessment of PD-L1/SP142 immunohistochemistry and TILs. Ten pathologists evaluated PD-L1/SP142 expression in a proficiency test comprising 28 primary TNBCs, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Introducing a new scoring system without training might not reflect the true potential of the scoring system. 37,38 Although 2 different variables are combined to produce H-score (percent positive cells and staining intensity), our results showed that interobserver reliability was as good for H-score if not slightly superior to PPS, as shown by the statistical analysis. One explanation might be that differences between readers for low positive cases have a lesser impact on the total H-score than differences in strongly positive cases because the former percent is multiplied by 1 and the latter by 3.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Introducing a new scoring system without training might not reflect the true potential of the scoring system. 37,38 Although 2 different variables are combined to produce H-score (percent positive cells and staining intensity), our results showed that interobserver reliability was as good for H-score if not slightly superior to PPS, as shown by the statistical analysis. One explanation might be that differences between readers for low positive cases have a lesser impact on the total H-score than differences in strongly positive cases because the former percent is multiplied by 1 and the latter by 3.…”
Section: Discussionmentioning
confidence: 57%
“…In their study, however, there was no training for the readers. Introducing a new scoring system without training might not reflect the true potential of the scoring system 37,38 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the necessity of proper training of pathologists in the assessment of PD-L1 with SP142 is emphasized, as there is a large discrepancy in the interpretation of results between pathologists, especially in samples from metastases [19].…”
Section: Qualification For Treatmentmentioning
confidence: 99%
“…In contrast, in the NeoTRIPaPDL1 trial, no difference in pCR rates was observed between the PD-L1-positive and the PD-L1-negative groups [ 83 ]. Again, these contradictory results might partly be explained by the relatively high degree of inter-observer variability among pathologists in PD-L1 immunohistochemical assessment, as reported for both primary and metastatic TNBC [ 84 , 85 ].…”
Section: Current Biomarkers Used For the Clinical Decision Making Of ...mentioning
confidence: 99%